A novel mechanical ventilation heat recovery/heat pump system - Gillott, Mark C. (2000)
The trend towards improving building airtightness to save energy has increased the incidence of poor indoor air quality and associated problems, such as condensation on windows, mould, rot and fungus on window frames. Mechanical ventilation/heat recovery systems, combined with heat pumps, offer a means of significantly improving indoor air quality, as well as providing energy efficient heating and cooling required in buildings.